Síntese e estudo in silico de análogos de 2,3-Diidro-1H-1,5- Benzodiazepinas como potenciais antifúngicos e antioxidantes - Caiana, Elizeu Cordeiro (2021)
Benzodiazepines are seven-membered N-heterocyclic compounds that have a versatile structure, easy preparation and great pharmacological potential. In this sense, the present work describes the synthesis of 2,3-dihydro-1H-1,5-benzodiazepines for further evaluation in in vitro assays of antioxidant activity and antifungal activity, as well as in silico assays to investigate the clinical potential of the compounds. Among the synthesized analogues, the compounds Bdz2, Bdz5/5’, Bdz6/6’, Bdz7 and Bdz8/8’ are new. In an initial step, the optimal conditions for the synthesis of benzodiazepines in a reaction catalyzed by trifluoroacetic acid were found, which allowed the obtainment of compounds derived from substituted acetophenones (R2 = 3-OH, 4-OH and 4-Cl-3-NO2) in good to excellent yields (87 to 95%). The best reaction conditions were assigned to polar protic solvents (MeOH, EtOH) at room temperature. All compounds were characterized by FT-IR, 1H and 13C NMR, MS and melting point. In a later stage, when investigating the use of heterogeneous catalysts based on core@shell NPMs, a performance inferior to that presented by the synthesis via homogeneous catalysis was observed, having reached a maximum yield of only 31% for the classic benzodiazepine Bdz1 in reaction carried out under heating in a microwave reactor at 120 ºC. In the evaluation of antioxidant activity, the best results were presented by the hydroxylated derivatives Bdz3 (R1 = H; R2 = 4-OH) and Bdz6/6' (R1 = CH3; R2 = 4-OH), which in the CAT assay showed activity antioxidant superior to BHT and ascorbic acid standards. In the evaluation of antifungal activity, carried out in the first place for fungal species of the genus Sporothrix, the hydroxylated compounds showed better performance, with emphasis on the mixture of unprecedented regioisomers Bdz6/6', containing the methyl group in R1, with MIC values and CFM, which indicated an inhibitory action superior to that of the reference drug fluconazole. From the in silico study it was observed that all compounds had better oral bioavailability and lower toxicity than the commercial antifungal itraconazole, and the hydroxylated compounds had the best aqueous solubility and cell permeability profile. Overall, based on the results of in vitro and in silico assays, Bdz6/6’ proved to be a potential new antifungal candidate, administered orally.